Bonding Analysis of Compounds with Unusual Coordination of Carbon: Proposed Symmetric Systems with Six-Coordinate Carbon - BLEDA, ERDİ ATA; ALTUN, ZİKRİ (MDPI, 2020)
The possibility of carbon tetravalence in geometries other than tetrahedral and of carbon hypervalence has been taken seriously since the 1970s. Computational modeling and subsequent experimental validation have established the existence of molecules with carbon atoms with planar tetravalence and as many as six objects in carbon's coordination sphere. In this work, we develop insight into the nature of bonding to carbon in these unusual environs as provided by Bader's Atoms in Molecules (AIM) analysis of the electron density, along with the electron localization function (ELF) and the non-covalent index (NCI). We review several well-established systems (spiropentadiene dication, hexamethyl benzene dication, dimethanospiro[2.2]octaplane dication, and 1,8-dimethoxy-9-dimethoxyanthracene cation) and propose new D-2d-symmetric variants of a hexacoordinated species.
Keywords: AIM modeling; electron localization function; non-covalent interaction; carbon hypercoordination; PLANAR TETRACOORDINATE CARBON; PYRAMIDAL HEXAMETHYLBENZENE DICATION; HEXACOORDINATE CARBON; THEORETICAL DESIGN; ATOMS; BEARING; BORON; SPECTROSCOPY; MOLECULES; CHEMISTRY